Determination of Courier’s Routes Delivery for Distributing Parcels in Perak - Qian Hui, Ng; Mohd Salleh, Rohayu (Enhanced Knowledge in Sciences and Technology, 2022)
Courier services plays a significant role in transporting the parcels from one location to another and ensuring that the parcels reach the customer’s doorstep. Due to the rising demand for courier services, late delivery is a common delivery problem for courier companies. Meanwhile, the emergence of Covid-19 pandemic had brought a surge in demand for courier services. Hence, this study was applied route optimization for DHL Express to determine the shortest total distance and total average time spent to deliver the parcels effectively. It investigates the most effective method for DHL Express to employ as an optimization tool to optimize the delivery route for their company. Genetic Algorithm and Tabu Search were proposed in this study in order to solve the travelling salesman problem (TSP) using Python software. The main assumption of this problem was that each parcel hub would be visited once and then returned to its origin. This study mainly focuses on 15 parcel hubs in Perak, with the data on total distance travelled and average time spent collected at 3 different times frames, namely 9.00 am, 1.00 pm and 6.00 pm. There are two optimal routes generated respectively in terms of total distance travelled and total average time spent for both methods. The performance of both methods was evaluated by shortest total distance travelled and minimum total average time spent. The results revealed that Genetic Algorithm outperformed Tabu Search in solving small sample size problem. Thus, DHL Express was recommended to use the suggested route to deliver the parcels in order to achieve cost-effectiveness, improve efficiency and whereby improve customer satisfaction.